Wide-range mass calibration for negative-ion DART mass spectrometry: $hJürgen H. Gross - Gross, Jürgen H. (European journal of mass spectrometry, 2014)
A method for accurate mass calibration covering a wide m/z range in negative-ion direct analysis in real time mass spectrometry (DART-MS) is described. It is ba...
Gesehen am 26.10.2020